Données préliminaires sur le zoobenthos du substrat meuble de la zone portuaire Constanţa - Țigănuș, Victoria (Cercetări Marine - Recherches Marines, 2026)
The benthic fauna of Constanta harbor has been investigated. According to the heavy pollution the fauna is extremely scarce, represented mainly by Nematoda and Polychaeta (Neanthes sunccinea. Polydora ciliata, Capitella capitata, Spio filicornis).